PENERAPAN APLIKASI KAHOOT SEBAGAI MEDIA EVALUASI INTERAKTIF DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - B. Syukroni Baso; Abdul Sakti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of implementing Kahoot as an interactive evaluation medium in Indonesian language learning at the elementary school level. The research involved classroom observations, student perception questionnaires, and learning outcome tests conducted before and after the implementation of Kahoot. Quantitative data were analyzed by calculating the percentage increase in learning outcomes, while qualitative data were obtained through observations of students’ learning behaviors and interpretations of questionnaire responses. The results indicate that the use of Kahoot increased student engagement by up to 92%, learning motivation by 88%, enjoyable evaluation experiences by 90%, and understanding of Indonesian language material by 84%. These findings confirm that Kahoot functions not only as a digital evaluation tool but also as an effective pedagogical strategy that strengthens Indonesian language literacy and creates a more active, collaborative, and engaging learning experience aligned with the demands of contemporary education.